NON SECULARIZATION OF MARRIAGE LEGAL PROCEDURE BASED ON BELIEF IN ONE ALMIGHTY GOD IN INDONESIA - Burhanudin Harapah; Solikhah Muslich Sugiyono; Luthfiyah Trini Hastuti (Faculty of Law, Universitas Sebelas Maret, 2020)
When disputing in court, non-Muslim citizens use positive laws established by the state that do not involve their religious beliefs. Philosophically, this is on the contrary to the constitution, which states that the country is based on belief in one Almighty God. Moreover, in every decision, judges are formally required to begin with